Endoscopic Vacuum Therapy for iatrogenic esophageal perforation in a child - Takwa Mili; Intissar Chibani; Awatef Charieg; Nizar Nouaili; Yosra Ben Ahmed; Tarek Boukesra; Faouzi Nouira; Said Jlidi (Elsevier, 2022)
Esophageal perforation (EP) has historically been a devastating condition resulting in high morbidity and mortality. The use of endoluminal therapies to treat esophageal leaks and perforations has grown exponentially over the last decade and offers many advantages over traditional surgical intervention in the appropriate circumstances. Here, we present a case of iatrogenic perforation of esophagus successfully treated with Endoscopic Vacuum Therapy (EVT) in a 6-year-old female patient.